(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The present study “Occupational stress on High school teachers towards continuous and comprehensive evaluation pattern” perceived causes of stress among high school teachers towards continuous and comprehensive evaluation. Main purpose of this study is to examine occupational stress among male and female teachers with 14 years and above experience. Identification of best predictors of stress of teachers towards continuous and comprehensive evaluation programme.